2022
DOI: 10.3390/cancers15010243
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Methylome and Transcriptome Characterization Identifies SERINC2 as a Tumor-Driven Gene for Papillary Thyroid Carcinoma

Abstract: Most papillary thyroid carcinomas (PTCs) can be diagnosed preoperatively by routine evaluation, such as thyroid ultrasonography and fine-needle aspiration biopsy. Nevertheless, understanding how to differentiate indolent thyroid tumors from aggressive thyroid cancers remains a challenge, which may cause overtreatment. This study aimed to identify papillary thyroid cancer-specific indicators with whole-genome DNA methylation and gene expression profiles utilizing Infinium Methylation EPIC BeadChip (850k) and RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Therefore, accurately identifying malignancy of thyroid tumors, especially those with indeterminate cytology, is essential for avoiding overtreatment and controlling tumor metastasis, which could benefit from supportive biomarkers. In this study, we identified RUNX1 methylation with high credibility and good accuracy in differentiating early-stage PTC cases from BTN subjects, suggesting it as a potential biomarker to aid the diagnostic process [47,48].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Therefore, accurately identifying malignancy of thyroid tumors, especially those with indeterminate cytology, is essential for avoiding overtreatment and controlling tumor metastasis, which could benefit from supportive biomarkers. In this study, we identified RUNX1 methylation with high credibility and good accuracy in differentiating early-stage PTC cases from BTN subjects, suggesting it as a potential biomarker to aid the diagnostic process [47,48].…”
Section: Discussionmentioning
confidence: 77%
“…Both benign and malignant thyroid tumors have abnormal cell proliferation, DNA mutations or epigenetic changes, and large tumors are often accompanied by abundant angiogenesis and energy consumption [45]. Nevertheless, benign tumors don't invade neighboring tissue or metastasize and can be safely monitored with no or minimal treatment, whereas malignant tumors are usually aggressive and have a chance of recurrence and metastasis after resection of the focus, seriously threatening the life and health of patients [46,47]. Therefore, accurately identifying malignancy of thyroid tumors, especially those with indeterminate cytology, is essential for avoiding overtreatment and controlling tumor metastasis, which could benefit from supportive biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation, the most widely studied epigenetic mechanism, varies in different cancers, and is notably altered in thyroid cancer [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Now, the role of DNA methylation in cancer is being widely studied to determine markers that might guide treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The BRAF V600E mutation is common in thyroid cancer [ 13 , 15 , 16 , 18 , 22 , 23 , 25 ], as is DNA methylation [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. However, the interaction or association between them is not well-studied.…”
Section: Introductionmentioning
confidence: 99%